2018
DOI: 10.1073/pnas.1719666115
|View full text |Cite
|
Sign up to set email alerts
|

A neurochemical hypothesis for the origin of hominids

Abstract: It has always been difficult to account for the evolution of certain human characters such as language, empathy, and altruism via individual reproductive success. However, the striatum, a subcortical region originally thought to be exclusively motor, is now known to contribute to social behaviors and "personality styles" that may link such complexities with natural selection. We here report that the human striatum exhibits a unique neurochemical profile that differs dramatically from those of other primates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 114 publications
(139 reference statements)
3
59
0
Order By: Relevance
“…Raghanti et al. () demonstrated that the human striatum, a region of the brain modulating social behavior, exhibits unique neurochemical profile compared to other primates. Sousa et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raghanti et al. () demonstrated that the human striatum, a region of the brain modulating social behavior, exhibits unique neurochemical profile compared to other primates. Sousa et al.…”
Section: Resultsmentioning
confidence: 99%
“…Stimpson et al (2016) has identified an evolutionary change in the serotonergic innervation of the amygdala between chimpanzees and bonobos, and suggested that it has led to differences in the aggressive behaviors, cautious temperaments, risk preferences, and performances on "theory of mind" tasks even between these closely related species. Raghanti et al (2018) demonstrated that the human striatum, a region of the brain modulating social behavior, exhibits unique neurochemical profile compared to other primates. Sousa et al (2017) have reported that a type of dopaminergic interneuron exclusively exists in the human neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…Modern humans are characterized by great intrasocial compassion, are motivated by concern about the welfare of out-group individuals, and display a clear tendency to act in concert, to the extent that Homo Sapiens has been labeled as ‘ultra-social’ 7 . This trait is of special relevance, as it has been argued to underlie other singular traits of humans, such as their enhanced verbal communicative skill 6-10 .…”
Section: Introductionmentioning
confidence: 99%
“…The sequencing of two Neanderthal genomes from Altai (Siberia) 11 and Vindija (Croatia) 12 and a Denisovan from Alta 13 has made available genomic data to provide new insights into the discussion of the evolution of social cognition, complementing the archaeological evidence. Today, various hypothese 6, 10, 14, 15 still offer different explanations and timelines for the emergence of prosociality, ranging from the Pan-Homo split to later stages of human evolution, such as the split between Neanderthals and Denisovans on the one hand, and Modern Humans on the other. The critical effect of OXT and AVP on pair-bonding has led some of the authors of the aforementioned theories, most prominently, 14 , to ascribe to them a key role in the emergence of human social behavior, while others have challenged the centrality of OXT and AVP in this shift in favor of other hormones, such as P-endorphines and dopamin 10, 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation